Upper limit on the cosmic-ray photon flux above 10^19 eV using the surface detector of the Pierre Auger Observatory - Collaboration, TPA (2007)
A method is developed to search for air showers initiated by photons using data recorded by the surface detector of the Auger Observatory. The approach is based on observables sensitive to the longitudinal shower development, the signal risetime and the curvature of the shower front. Applying this method to the data, upper limits on the flux of photons of 3.8*10^-3, 2.5*10^-3, and 2.2*10^-3 km^-2 sr^-1 yr^-1 above 10^19 eV, 2*10^19 eV, and 4*10^19 eV are derived, with corresponding limits on the fraction of photons being 2.0%, 5.1%, and 31% (all limits at 95% c.l.). These photon limits disfavor certain exotic models of sources of cosmic rays. The results also show that the approach adopted by the Auger Observatory to calibrate the shower energy is not strongly biased by a contamination from photons.